(untitled) (Movimenta (ISSN 1984-4298), 2016)
This edition of Movimenta brings the abstracts of International Workshop BR-UK Dance Medicine & Science Network. The Proceedings reveals the research production of more than thirty researchers from different professions that in August 2016 joined in Goiânia, Brazil, in the workshop "The Potentials and Challenges of Research in Dance Medicine & Science: building innovation collaborations between United Kingdom and Brazil". They spent five days discussing the possibilities of creating a BR-UK Dance Medicine & Science Network that could collaborate in the next 15 years, creating services, research and educational opportunities for dancers, the professionals that work with dance and the general population.